Emptiness in the early Prajñāpāramitā and the Tathāgatagarbha scriptures - Yang, C (2023)
Emptiness (Skt. śūnyatā; Chs. kong 空/kongxing 空性; Tib. stong pa nyid) is undoubtedly one of the most important concepts in the history of Mahāyāna Buddhism in India, East Asia, and Tibet, and the concept as it appears in a wide range of periods and geographical regions has been investigated in depth in modern scholarship. However, there is a one conspicuous omission: there has been no comprehensive book-length study focusing on the idea of emptiness across Mahāyāna sūtras, particularly between the beginning of the Common Era to the foundation of the Gupta Empire in the early fourth century CE, which is arguably the most formative period of Mahāyāna Buddhism in India.